Pharmacological comparison of swelling-activated excitatory amino acid release and Cl(−) currents in cultured rat astrocytes - Abdullaev, Iskandar F (Blackwell Science Inc, 2006)
Ubiquitously expressed volume-regulated anion channels (VRACs) are chloride channels which are permeable to a variety of small organic anions, including the excitatory amino acids (EAAs) glutamate and aspartate. Broad spectrum anion channel blockers strongly reduce EAA release in cerebral ischaemia and other pathological states associated with prominent astrocytic swelling. However, it is uncertain whether VRAC serves as a major pathway for EAA release from swollen cells. In the present study, we measured swelling-activated release of EAAs as d-[(3)H]aspartate efflux, and VRAC-mediated Cl(−) currents by whole-cell patch clamp in cultured rat astrocytes. We compared the pharmacological profiles of the swelling-activated EAA release pathway and Cl(−) currents. The expression of candidate Cl(−) channels was confirmed by RT-PCR. The maxi Cl(−) channel (p-VDAC) blocker Gd(3+), the ClC-2 inhibitor Cd(2+), and the MDR-1 blocker verapamil did not affect EAA release or VRAC currents. An antagonist of calcium-sensitive Cl(−) channels (CaCC), niflumic acid, had little effect on EAA release and only partially inhibited swelling-activated Cl(−) currents. The phorbol ester PDBu, which blocks ClC-3-mediated Cl(−) currents, had no effect on VRAC currents and up-regulated EAA release. In contrast, DCPIB, which selectively inhibits VRACs, potently suppressed both EAA release and VRAC currents. Two other relatively selective VRAC inhibitors, tamoxifen and phloretin, also blocked the VRAC currents and strongly reduced EAA release. Taken together, our data suggest that (i) astrocytic volume-dependent EAA release is largely mediated by the VRAC, and (ii) the ClC-2, ClC-3, ClC-4, ClC-5, VDAC, CaCC, MDR-1 and CFTR gene products do not contribute to EAA permeability.